Z życia romantyka. Dwa nieznane listy Władysława Wężyka: do Lucjana Siemieńskiego i do Eleonory Karwickiej - Dambek-Giallelis, Zofia (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
The article includes the first edition of two letters written by Władysław Wężyk, a forgotten writer and activist from the 1840s. The first one, discovered in the Stefanyk National Science Library in Lviv, Ukraine, documents the young domestic writers’ interest in Towianism. In the second one, kept in the Jagiellonian Library, Wężyk expresses his intentions towards his future wife and considers his life plans, which include his participation in the awaited uprising. The newly-discovered letters document both the initial enthusiasm in the country towards Towiański’s doctrine and the author’s involvement in the conspiracy network in the 1840s.